MEDIA UNTUK PEMBELAJARAN KOSA KATA BAHASA INGGRIS DI SEKOLAH DASAR - ., Farikah (Majalah Transformatika, 2010)
English  is  the  first  foreign  language  that  is  taught  in Elementary School in Indonesia. As a foreign language, English vocabulary is very important. Teaching vocabulary in Elementary Schools needs various media that make the students active. Key words: Various Media, Vocabulary.